Cytokine Signaling in Skeletal Muscle Wasting. (May 2016) - Zhou, Jin; Liu, Bin; Liang, Chun; Li, Yangxin; Song, Yao-Hua
Abstract : Skeletal muscle wasting occurs in a variety of diseases including diabetes, cancer, Crohn's disease, chronic obstructive pulmonary disease (COPD), disuse, and denervation. Tumor necrosis factor α (TNF-α) is involved in mediating the wasting effect. To date, a causal relationship between TNF-α signaling and muscle wasting has been established in animal models. However, results from clinical trials are conflicting. This is partly due to the fact that other factors such as TNF-like weak inducer of apoptosis (TWEAK) and interleukin 6 (IL-6) are also involved in skeletal muscle wasting. Because muscle wasting is often associated with physical inactivity and reduced food intake, therapeutic interventions will be most effective when multiple approaches are used in conjunction with nutritional support and exercise. Trends: Muscle wasting is the result of an imbalance between anabolic and catabolic metabolism due to inflammation, physical inactivity, and inadequate nutrition. TNF-α, IL-6, and TWEAK shift the metabolism balance toward a catabolic process. However, current therapies such as neutralizing antibodies/decoy receptors against TNF-α, IL-6, and nonsteroidal anti-inflammatory drugs had limited success when used alone. These specific therapies will be more successful when combined with nutritional support, appetite stimulators, and exercise, because combinatorial approaches will not only inhibit protein degradation but also promote protein synthesis. Clinical trials are warranted and will yield more conclusive results by measuring cytokine levels from each patient prior to treatment.